EFFECT OF WORK ENVIRONMENT, COMPENSATION, WORK DISCIPLINE AND WORK ETHOS TO PERFORMANCE OF EMPLOYEE AGENCY AND HUMAN RESOURCES DEVELOPMENT MENTAWAI ISLANDS DISTRICT - Yass Andria; Martin Welly; Metayana Oktavia; Nofyadi Nofyadi (SEAN Institute, 2022)
This study aims to determine the effect of the work environment, compensation, work discipline, and work ethic on employee performance. This research is motivated by a work environment that is felt to be less supportive in carrying out work, perceived compensation is still low, awareness of attendance at work is still low, obedience to rules and ethical behavior is still being violated, and employee performance is still unstable and tends to low in BKPSDM employees of Mentawai Islands Regency. This type of research uses a quantitative approach with multiple linear regression method. Data collection techniques with question naires, observations and interviews. The respondents of this study were 45 employees at BKPSDM Mentawai Islands Regency. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0 program. From the results of this study it was found that partially the work environment has a significant effect on employee performance, compensation has a significant effect on employee performance, work discipline has a significant effect on employee performance, work ethic has a significant effect on employee performance, and work environment, compensation, work discipline and work ethic jointly have a significant effect on employee performance at BKPSDM Mentawai Islands Regency